Focus on the Different Projects of Telemedicine Centered on the Elderly In France - Zulfiqar, Abrar A.; Hajjam, Amir; Andrés, Emmanuel (Current Aging Science, 2018)
Telemedicine is now in vogue, allowing computer and communication tools to be deployed in different fields of health, such as Cardiology, Dermatology, areas in which it has received interest, and in international studies. As the population ages, older people are increasingly concerned about this innovative practice. This is a narrative review of both the literature and Internet pertaining to telemedicine projects within the field of geriatric subjects in France. Since the beginning of the 2000’s, several telemedicine projects and trials focused on chronic heart failure have been developed in the elderly, and also in the field of dermatology. The potential contribution of second-generation telemedicine projects in terms of mortality, morbidity, and the number of hospitalizations avoided is currently under study. Their impact in terms of health economics is likewise being investigated, taking into account that the economic and social benefits brought up by telemedicine solutions were previously validated by the original telemedicine projects. We take a look at telemedicine projects in France concerning the elderly.
Keywords: Telemedicine